VLSI Design for Home Automation System - Wong, Wen Cong; Mat Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2023)
The home automation system is designed to enhance the comfort, convenience, and security of a household by integrating various subsystems such as lighting control, temperature regulation and security monitoring. The proposed solution involves integrating a security system, lighting system, HVAC system and water tank system into Very Large-Scale Integration (VLSI) technology. The design was optimized for area and timing using the 32 nm Complementary Metal-Oxide Semiconductor (CMOS) technology. The Register Transfer Level (RTL) logic design, along with its corresponding testbench, was written in Verilog Hardware Descriptive Language (HDL) code. The design underwent pre-functional verification using ModelSim-Altera and post-functional verification using Synopsys VCS. Once the design passed verification, it was converted into a gate-level netlist and underwent physical synthesis. the proposed design demonstrated successful operation by generating accurate outputs for the actuators based on the input signals from the sensors. This indicates that the design is functioning as intended. The final layout of the design was implemented with an area of 659.95 μm2, indicating efficient use of physical resources. The total power consumption of the design was measured at 206.35 μW, reflecting optimized power usage. The design exhibited a positive timing slack of 0.46 ns, indicating that the timing requirements were comfortably met. Furthermore, the design passed the physical verifications with no reported Design Rule Check (DRC) violations or Layout Versus Schematic (LVS) violations.